Chilblain Lupus: An Overview - Maulida, Aileen Aisyah (LOCUS MEDIA PUBLISHING, 2025)
CHLE is a form of chronic CLE that is associated with disease progression to SLE. While both CLE and SLE are subtypes of lupus, SLE has a significantly higher rate of both morbidity and mortality. This means that although CHLE is considered a rare form of CLE, it is important for clinicians to be able to recognize this disease and differentiate it with other similar diagnoses, such as regular chilblain. This can be aided by using the Mayo Clinic Criteria, which is a diagnostic criteria for CHLE.